Character sums associated with nonhomogeneous Beatty sequences for quadratic common difference - Low, Chee Wai; Sapar, Siti Hasana; Deraman, Fatanah; Mohamat Johari, Mohamat Aidil (Penerbit UTM Press, 2025)
Beatty sequence is a special type of sequence by taking the floor of the positive value of an irrational number. This paper will find an explicit bounds of character sums associated with non-homogeneous Beatty sequence in quadratic fields. Next, we obtained the cardinality of character sums associated with composite moduli. Finally, we found the estimated bound of character sums associated with composite moduli by using the discrepancy and the cardinality.